Knowledge of lung cancer symptoms and risk factors in the UK: development of a measure and results from a population-based survey. Issue 5 (16th March 2012) - Simon, Alice E; Juszczyk, Dorota; Smyth, Nina; Power, Emily; Hiom, Sara; Peake, Michael D; Wardle, Jane
Abstract : Objectives: To develop and validate a Lung Cancer Awareness Measure (Lung CAM) and explore the demographical and social predictors of lung cancer awareness in the general population. Methods study 1: Symptoms and risk factors for lung cancer were identified from the medical literature and health professional expertise in an iterative process. Test–retest reliability, internal reliability, item analyses, construct validity and sensitivity to changes in awareness of the Lung CAM were assessed in three samples (total N=191). Results study 1: The Lung CAM demonstrated good internal (Cronbach's α=0.88) and test–retest reliability (r=0.81, p<0.001). Validity was supported by lung cancer experts scoring higher than equally educated controls (t(106)=8.7, p<0.001), and volunteers randomised to read lung cancer information scoring higher than those reading a control leaflet (t(81)=3.66, p<0.001). Methods study 2: A population-based sample of 1484 adults completed the Lung CAM in a face-to-face, computer-assisted interview. Results study 2: Symptom awareness was low (average recall of one symptom) and there was little awareness of risk factors other than smoking. Familiarity with cancer, and being from a higher socioeconomic group, were associated with greater awareness. Conclusions: Using a valid and reliable tool for assessing awareness showed the UK population to have low awareness of lung cancer symptoms and risk factors. Interventions to increase lung cancer awareness are needed to improve early detection behaviour.